(untitled) (Journal of Management and Educational Sciences, 2026)
The purpose of this study is to examine the relationships between school administrators’ communication skills, school climate, and teachers’ psychological well-being levels according to teachers’ perceptions, and to determine the extent to which administrators’ communication skills and school climate predict teachers’ psychological well-being. The research was designed as a correlational survey model. The sample of the study consisted of 261 teachers working in vocational high schools in the Altındağ district of Ankara. The Communication Skills Scale, Psychological Well-Being Scale, and School Climate Scale were used as data collection tools. Descriptive statistics, independent samples t-test, one-way analysis of variance (ANOVA), Pearson’s moment correlation analysis, and multiple linear regression analysis techniques were used in the analysis of the data. The research findings show that there is a positive and significant relationship between school administrators’ communication skills and teachers’ psychological well-being; however, there is a negative and significant relationship between perceptions of school climate and psychological well-being. According to the results of the multiple linear regression analysis, when administrators’ communication skills and school climate are considered together, they significantly predict teachers’ levels of psychological well-being. When examining the regression coefficients, it was determined that the strongest variable in predicting teachers’ psychological well-being was administrators’ communication skills. The results obtained reveal that managerial communication and the organizational context of the school play a critical role in enhancing teachers’ psychological well-being.